Deamination of lysine in soy sauce by reaction with active carbonyl compounds produced by Maillard reaction (Jurnal Teknologi Pangan, 2013)
The development of a brown colour during the thermal treatment of many foods, such  as  coffee,  roasted  beef, soysauce  or  evaporated  milk,  mainly  originates  from interaction  between  reducing  carbohydrates  and  amino  acids,  known  as  the Maillard reaction. It is commonly known at present that one of the causes of changes in colour, aroma,  flavor  and  nutritional  value  of  food  products. The Maillard  reaction  involves condensation, dehydration and polymerization.  As a result of this complex reaction, a variety of by products, intermediates and brown pigment. An  amino-carbonyl  reaction  in  soysauce  yielded  a  rapid  brown  coloration.  An apparent  decrease  in  the  free  amino  group,  determined  by  the  TNBS  method,  was observed  to  be  associated  in  parallel  with  the  brown pigment  formation  by  UV-Vis spectrum,  amino  acids  by  HPLC,  Protein  content  by  Lowry  method,  pH  and  reducing sugar. “Moromi”, moromi with heating and soysauce were examined to effect Maillard reaction.  The  positive  effect  of  sugar  on  browning  suggested  that  lysine  content decreased from 1.18% to 0.69%, free amino group decreased from 3.16 mg/ml to 2.27 mg/ml  and  their  UV-Vis  spectrum    in range  400  nm.  These  results  indicate  that ε-amino  group  of  lysine  in  protein  could  easily  be  determined  by  the  amino-carbonyl reactionKey words : Maillard reaction, soysauce, brown pigment, lysine